Intraorganizational Communication and Job Satisfaction Among Flemish Hospital Nurses: An Exploratory Multicenter Study. (January 2018) - Vermeir, Peter; Downs, Cal; Degroote, Sophie; Vandijck, Dominique; Tobback, Els; Delesie, Liesbeth; Mariman, An; De Veugele, Myriam; Verhaeghe, Rik; Cambré, Bart; Vogelaers, Dirk
Intraorganizational communication affects job satisfaction and turnover. The goal of this study was to explore relationships between communication and job satisfaction, intention to leave, and burnout among Flemish hospital nurses. A multicenter questionnaire study was conducted in three hospitals using the Communication Satisfaction Questionnaire, the Turnover Intention subscale of the Questionnaire on the Experience and Evaluation of Work, and the Maslach Burnout Inventory. A visual analog scale measured job satisfaction. The mean job satisfaction score was 7.49/10 (±1.43). Almost 7% of nurse participants (93/1, 355) reported a high intent to leave, and 2.9% of the respondents (41/1, 454) had a score indicative of burnout. All dimensions of communication were associated with job satisfaction. A low score on any dimension of communication satisfaction, except "Relationship With Employees, " was associated with higher intent to leave and burnout. Study findings support the need for management interventions to enhance efficient communication and ensure high-quality care and patient safety.